Analysis of Hospital-Based Cancer Registration Training Readiness Using Blended Learning Method in the National Cancer Center Indonesia, Dharmais Cancer Hospital - Agustina, Julyanti; Djasri, Hanevi (Academic Hospital Journal, 2023)
Background: Cancer registration produces statistical information on cancer that complies with international standards so that it can be used as a baseline for taking cancer policy directions. The quality of the data can be affected by the officers who carry it out. Hospital-Based Cancer Registration Training in Indonesia has been held since 2016 to increase the capacity of cancer registration implementation. Since the pandemic, online methods have been increasingly used in the world, not only in education but also in health sector . In addition, the blended learning method has becomebecome an option because it is more effective for delivering material that requires interaction with the instructor. Cancer registrars have an important role in the process of cancer registration activities in providing valid and accurate information so that to support performance, training is needed to increase the capacity of cancer registrars. Dharmais Cancer Hospital has had a Hospital-Based Cancer Registration Training program with the aim of achieving the competencies needed in cancer registration. This study aims to analyze the readiness of the blended learning method of hospital-based cancer registration training by the National Cancer Center Indonesia, Dharmais Cancer Hospital. Methods: The research design was carried out in the form of quantitative descriptive where data collection was in the form of questionnaires to the research subjects according to the inclusion criteria. The inclusion criteria for research subjects were training instructors, training organizers, cancer registration implementers, and leaders who were responsible for cancer registration. The research was conducted at the National Cancer Center Indonesia, Dharmais Cancer Hospital from April to November 2022. Data will be analyzed using SPSS. Results: We analysed the 35 respondents with the results were mostly female (80%), bachelor degree (51.4%), 30-39 years old (40%), never been cancer registration trainer (71.4%), and ever heard about about cancer registration training (82,9%). There were three variable that had mean higher than overall mean which technology (3.95), self development (3.86), and training curriculum (3.98). However the innovation (3.61) and training organizer (3.17) were less then overall mean. Conclusion: Dharmais Cancer Hospital has been ready but need improvements to have cancer registration training using blended learning. Innovation factor and training organizer should be improved.